Penerapan Steganografi LSB dan Enkripsi AES untuk Keamanan Data Rahasia pada Gambar Digital - Set, Faustina Maria C. Baria; Bana, Citra Maria N.; Anunut, Maria Angliadi; Costa, Demetriana Da; Niis , Yulita (PT. Publikasiku Academic Solution, 2025)
In the digital era, the need for data protection systems has become increasingly urgent due to growing threats to privacy, such as eavesdropping and information theft. This study aims to design and implement a data protection system that combines Least Significant Bit (LSB)-based steganography with Advanced Encryption Standard (AES-256) encryption to secure confidential data within digital images. This research employs an applied quantitative experimental approach with a laboratory design, involving the encryption of text data using AES-256, followed by embedding the encrypted data into PNG-format images using the LSB technique. Evaluation is conducted by measuring image quality using PSNR and MSE, as well as assessing the success of data extraction, decryption, and process efficiency. The results show that the system successfully maintains the visual quality of the image, with PSNR values exceeding 58 dB, indicating no significant visual alterations. Data extraction and decryption achieved a 100% success rate, while the execution time for each process was less than 0.02 seconds, demonstrating high efficiency. The combination of steganography and encryption proves to provide an effective layered protection mechanism for confidential data. In conclusion, this system is feasible for implementation as a digital image-based data security solution, with potential for further development through adaptive steganography methods and the integration of additional encryption algorithms.